Engineering of recombinant Escherichia coli cells co‐expressing poly‐γ‐glutamic acid (γ‐PGA) synthetase and glutamate racemase for differential yielding of γ‐PGA. Issue 6 (6th August 2013) - Cao, Mingfeng; Geng, Weitao; Zhang, Wei; Sun, Jibin; Wang, Shufang; Feng, Jun; Zheng, Ping; Jiang, Anna; Song, Cunjiang
Summary Poly‐γ‐glutamic acid (γ‐PGA) is a promising environmental‐friendly material with outstanding water solubility, biocompatibility and degradability. However, it is tough to determine the relationship between functional synthetic enzyme and the strains' yield or substrate dependency. We cloned γ‐PGA synthetase genes pgsBCA and glutamate racemase gene racE from both L‐glutamate‐dependent γ‐PGA‐producing Bacillus licheniformis NK‐03 and L‐glutamate‐independent B. amyloliquefaciens LL3 strains. The deduced RacE and PgsA from the two strains shared the identity of 84.5% and 78.53%, while PgsB and PgsC possessed greater similarity with 93.13% and 93.96%. The induced co‐expression of pgsBCA and racE showed that the engineered Escherichia coli strains had the capacity of synthesizing γ‐PGA, and LL3 derived PgsBCA had higher catalytic activity and enhanced productivity than NK‐03 in Luria–Bertani medium containing glucose or L‐glutamate. However, the differential effect was weakened when providing sufficient immediateness L‐glutamate substrate, that is, the supply of substrate could be served as the ascendance upon γ‐PGA production. Furthermore, RacE integration could enhance γ‐PGA yield through improving the preferred d‐glutamate content. This is the first report about co‐expression of pgsBCA and racE from the two Bacillus strains, which will be of great value for the determination of the biosynthetic mechanism of γ‐PGA.